Stress behaviour of tailor welded blanks for dissimilar metals using finite element method - Lee, Chee Wor (2013)
This project presents the stress analysis on tailor welded blanks for dissimilar metals using finite element method. The application of the tailor welded blanks in automotive industries has a large potential and the critical location on the tailor welded blanks based on the stress analysis is important. The structural modeling of the tailor welded blanks is developed using computer aided design software. The method used for tailor welded blanks are later welding. The effect of different materials combination and different configuration on tailor welded blanks on welding behavior is another importance of this study. Finite element method is used to investigate the stress on the tailor welded blanks. Goldak’s double ellipsoid source model is used as the heat source model of the investigation. The changes of power in current and voltages, dissimilar metals of aluminium and steel; and the plate-configuration, L-configuration and T-configuration are investigated in this study. The increase of power increases the hot affected zone and distortion of the plate. The heat is dissipated faster at the aluminium plate compared to steel plate makes the stress concentrated at the steel plate. The stress is distributed outside the welding line for the T-configuration due to the fusion process is not complete.